2008
DOI: 10.1002/hipo.20487
|View full text |Cite
|
Sign up to set email alerts
|

The human hippocampus at 7 T—In vivo MRI

Abstract: The human hippocampus plays a central role in various neuropsychiatric disorders, such as temporal lobe epilepsy (TLE), Alzheimer's dementia, mild cognitive impairment, and schizophrenia. Its volume, morphology, inner structure, and function are of scientific and clinical interest. Magnetic resonance (MR) imaging is a widely employed tool in neuroradiological workup regarding changes in brain anatomy, (sub-) volumes, and cerebral function including the hippocampus. Gain in intrinsic MR signal provided by highe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
75
0
2

Year Published

2009
2009
2017
2017

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 80 publications
(79 citation statements)
references
References 31 publications
2
75
0
2
Order By: Relevance
“…Indeed, studies in schizophrenia that show a decline in the hippocampal cell viability marker ( N -acetylaspartate) levels ( 24 ) and hypermetabolism without volumetric changes ( 25 ) suggest that sensitivity to preclinical morphology may be key in establishing disease presence, disease progression, and, by implication, treatment response ( 26 ). Early visualization of signal intensity changes that may refl ect disruptions to hippocampal morphology requires high spatial resolution and contrast typically afforded only by 7.0-9.4-T fi eld strengths and high-element-count coil arrays ( 20,27,28 ). Although together these advanced imaging capabilities facilitate approximately 200-m m spatial resolution in 10-20 minutes, neither of two recent studies ( 20,28 ) demonstrated the ability of 7.0-T MR imaging to depict the DGCL.…”
Section: Mr Imagingmentioning
confidence: 99%
“…Indeed, studies in schizophrenia that show a decline in the hippocampal cell viability marker ( N -acetylaspartate) levels ( 24 ) and hypermetabolism without volumetric changes ( 25 ) suggest that sensitivity to preclinical morphology may be key in establishing disease presence, disease progression, and, by implication, treatment response ( 26 ). Early visualization of signal intensity changes that may refl ect disruptions to hippocampal morphology requires high spatial resolution and contrast typically afforded only by 7.0-9.4-T fi eld strengths and high-element-count coil arrays ( 20,27,28 ). Although together these advanced imaging capabilities facilitate approximately 200-m m spatial resolution in 10-20 minutes, neither of two recent studies ( 20,28 ) demonstrated the ability of 7.0-T MR imaging to depict the DGCL.…”
Section: Mr Imagingmentioning
confidence: 99%
“…Imaging studies have used methods for identifying these hippocampal subfields through unfolding methods in high resolution functional MRI (Zeineh et al, 2000(Zeineh et al, , 2001Ekstrom et al, 2009) and high resolution in vivo (Mueller et al, 2007;Theysohn et al, 2009;Van Leemput et al, 2009) and ex vivo (Yushkevich et al, 2009) structural MRI mapping. These subfields are independent of subregional definitions of the hippocampus along its longitudinal axis (head, body, and tail) that are more readily evaluated in lower resolution imaging studies.…”
Section: Introductionmentioning
confidence: 99%
“…SAR mitigation strategies such as RF pulse elongation and bandwidth reduction provide modest power savings and can be applied to high-resolution imaging, but are, in general, of limited versatility and are insufficient to compensate for power levels at very high field. Limited reports from 7 T have presented 2D FSE images of the human head (7,8), but at the expense of the number of slices and with excess delay time for SAR reduction.Previous works have shown that reducing, and often modulating, the refocusing angles of the FSE echo train is a viable means of RF power reduction, contrast manipulation, and point spread function modification. A favorable nonlinear relationship between echo amplitude and refocusing angle (9) permits drastic power reductions with relatively minor signal penalties.…”
mentioning
confidence: 99%
“…SAR mitigation strategies such as RF pulse elongation and bandwidth reduction provide modest power savings and can be applied to high-resolution imaging, but are, in general, of limited versatility and are insufficient to compensate for power levels at very high field. Limited reports from 7 T have presented 2D FSE images of the human head (7,8), but at the expense of the number of slices and with excess delay time for SAR reduction.…”
mentioning
confidence: 99%